Our Challenges in an Extraordinary Case of AL Amyloidosis - *, Gomercic Palcic Marija; Luka, Vrbanic; Marija, Mandic Peric; Monika, Ulamec; Marijka, Sokcevic; Danica, Galesic Ljubanovic (Archives of Clinical and Medical Case Reports, 2019)
Background: Light-chain (AL) amyloidosis is a condition in which extracellular tissue deposition of protein derived from light chain immunoglobulin fragments can affect any organ in the body, and therefore has a variety of clinical manifestations, mimics variety of diseases and can easily be misdiagnosed. Case Presentation: This is a case of 79-year-old man with 9-year history of IgM monoclonal gammopathy of undetermined significance. Patient presented with right-sided effusion with pulmonary infiltrate. After antibiotic treatment the infiltrate resolved, but effusion progressed and appeared also on the left side. Extensive workup revealed generalized lymphadenopathy and no signs of any organ failure. Lymph node biopsy was analyzed applying Congo red, immunohistochemistry, immunofluorescence and electron microscope, and diagnosis of AL amyloidosis with monoclonal kappa chains was established. Conclusions: Since prognosis and natural history of the disease is dependent on time of discovery, it is important to raise suspicion for AL amyloidosis and use all available diagnostic tools and collaborate with appropriate institutions.